Factors Which Contribute to the Immunogenicity of Non-replicating Adenoviral Vectored Vaccines - Coughlan, Lynda (Frontiers in Immunology, 2020)
Adenoviral vectors are a safe and potently immunogenic vaccine delivery platform. Non-replicating Ad vectors possess several attributes which make them attractive vaccines for infectious disease, including their capacity for high titer growth, ease of manipulation, safety and immunogenicity in clinical studies, as well as their compatibility with clinical manufacturing and thermo-stabilization procedures. In general, Ad vectors are immunogenic vaccines, which elicit robust transgene antigen-specific cellular (namely CD8+ T cells) and/or humoral immune responses. A large number of adenoviruses isolated from humans and non-human primates, which have low seroprevalence in humans, have been vectorized and tested as vaccines in animal models and humans. However, a distinct hierarchy of immunological potency has been identified between diverse Ad vectors, which unfortunately limits the potential use of many vectors which have otherwise desirable manufacturing characteristics. The precise mechanistic factors which underlie the profound disparities in immunogenicity are not clearly defined and are the subject of ongoing, detailed investigation. It has been suggested that a combination of factors contribute to the potent immunogenicity of particular Ad vectors, including the magnitude and duration of vaccine antigen expression following immunization. Furthermore, the excessive induction of Type I interferons by some Ad vectors has been suggested to impair transgene expression levels, dampening subsequent immune responses. Therefore, the induction of balanced, but not excessive stimulation of innate signaling is optimal. Entry factor binding or receptor usage of distinct Ad vectors can also affect their in vivo tropism following administration by different routes. The abundance and accessibility of innate immune cells and/or antigen-presenting cells at the site of injection contributes to early innate immune responses to Ad vaccination, affecting the outcome of the adaptive immune response. Although a significant amount of information exists regarding the tropism determinants of the common human adenovirus type-5 vector, very little is known about the receptor usage and tropism of rare species or non-human Ad vectors. Increased understanding of how different facets of the host response to Ad vectors contribute to their immunological potency will be essential for the development of optimized and customized Ad vaccine platforms for specific diseases.